Liquid Biopsy on Lung Cancer - Fasya Az Zahra; Zhafira Rima Wanjaya; Lucky T.H Hutapea (CV. Jasa Sukses Abadi, 2023)
Pulmonology intervention has experienced rapid progress, especially in diagnosing and treating lung cancer. Pulmonology intervention itself can be defined as the science and art related to the ability to perform invasive procedures in the field of pulmonology both for diagnostic and treatment needs and for this requires additional training beyond the existing standard training programs in the field of pulmonary diseases. Diagnostic and therapeutic procedures included in pulmonary interventions are transthoracic needle aspiration (TTNA), transbronchial needle aspiration (TBNA), rigid bronchoscopy, endobronchial ultrasonography (EBUS), laser bronchoscopy, electroendobronchial surgery, argon-plasma coagulation (APC), cryotherapy, airway stenting, balloon bronchoplasty, endobronchial radiation (brachytherapy), pleuroscopy (medical thoracoscopy), photodynamic therapy, percutaneous dilated tracheostomy, transtracheal oxygen indwelling and image-guided thoracic intervention. For nodules larger (>4 cm) and peripherally located, a CT-guided percutaneous approach with transthoracic needle aspiration (TTNA) showed high sensitivity and specificity of 90% and 97%, respectively. However, this procedure has a risk of causing a pneumothorax with an incidence that varies between 17% - 33%. Furthermore, if the size of the nodule is <1.5 cm, the success rate will be smaller, namely 74.4%. Likewise with mediastinoscopy which has been a standard procedure for determining the mediastinal stage in lung cancer, even though it shows a high sensitivity of up to >90%, but the risk of causing fatal complications is injury to the large blood vessels, nerves, trachea and bronchi and esophagus. (<0.5%) and complications of pneumothorax (2.5%).